Integration of a specialist pharmacist-led multidisciplinary team in primary care: preventing strokes in people with atrial fibrillation across North East London - Riyaz Patel; Sotiris Antoniou; Shabana Ali; Mital Patel; Matt Kearney; Jagjot Kaur Chahal; John Robson; Paul Wright; Afzal Sohaib; Richard Clements; Angela Theodoulou (BMJ Open Quality)
Public Health England outlines a national ambition of anticoagulating 90% of eligible patients with atrial fibrillation (AF) by 2029. In 2019/2020, two out of three boroughs reviewed in this study were in the bottom 10% of boroughs compared with others within England. Stroke National Audit data for these three boroughs from 2019 to 2020 identified that in patients with known AF admitted to hospital with strokes, 37% were not anticoagulated. Evidence shows that one stroke can be prevented for every 25 patients with AF treated with anticoagulation, reducing the burden of stroke and stroke-related disabilities.In 2020, hospital specialist cardiovascular pharmacists were commissioned to identify patients with AF at high ischaemic risk (CHA2DS2VASc≥2) in three boroughs by working with general practitioners (GPs) and practice-based pharmacists. Using digital ‘proactive care frameworks’ created by UCLPartners and the Clinical Effectiveness Group, Queen Mary University of London, baseline searches of GP records enabled clinical teams to risk stratify and prioritise patients with AF for review. Patients not on anticoagulation were categorised as high risk and were reviewed for initiation of anticoagulation. The second priority was patients on dual antithrombotic therapy to determine if antiplatelet therapy could be stopped to minimise bleeding risk.At baseline (March 2020), nationally available data (extracted from CVDPREVENT) showed that 81% of patients with AF at high ischaemic risk across the three selected boroughs were anticoagulated. Repeated data extraction in March 2023, showed 94% of patients with AF at high ischaemic risk were anticoagulated, an absolute improvement of 13%, with 415 patients initiated on anticoagulant therapy over 3 years, translating to 17 strokes prevented. There was a 52% reduction in dual antithrombotic therapy, preventing an estimated three major bleeds.Improvements were achieved through a combination of specialist pharmacist reviews, GP and practice-based pharmacist training and virtual multidisciplinary reviews supporting the integration of specialists into a primary care setting to enable joined-up pathways for effective stroke prevention.